On The Decay Energy of Lotka-Volterra Reaction-Diffusion Competition Model - Dadang Amir Hamzah (Jurnal Rekayasa Teknologi dan Sains Terapan, 2018)
In this paper we consider Lotka-Volterra system. It describes competition of two species. We explore conditions which guarantee the coexistence of two populations in the system. Energy method is employed to derive the conditions. Numerical example is presented to support the theory.